Kepailitan Terhadap Perseroan Perorangan - Curniawaty, Tety; Ichsan, Rully Ardika (Media Hukum Indonesia (MHI), 2024)
This research aims to analyze the legal implications of bankruptcy on individual companies (perseroan perorangan) within Indonesia's legal system. Introduced through Law Number 11 of 2020 on Job Creation, individual companies offer micro and small business actors the convenience of forming a legal entity with limited liability. However, the bankruptcy mechanisms for individual companies pose several issues, including the legal protection of creditors and the enforcement of the principle of separating personal and corporate assets. This study employs a normative juridical method with a statutory and conceptual approach.The research findings indicate that although individual companies hold the status of a legal entity, the implementation of creditor protection often faces challenges due to a lack of asset transparency and verification. Furthermore, there is a potential misuse of this legal entity type to evade financial responsibilities. The study also examines whether there are differences in bankruptcy regulations between individual companies and limited liability companies, which are governed by Law Number 40 of 2007 on Limited Liability Companies. It concludes that while individual companies provide advantages in ease of establishment, more detailed regulations on bankruptcy are essential to ensure legal certainty for stakeholders.